2020
DOI: 10.1029/2020rs007077
|View full text |Cite
|
Sign up to set email alerts
|

Quiet Time Ionopheric Irregularities Over the African Equatorial Ionization Anomaly Region

Abstract: This paper investigated variations of quiet time ionospheric irregularities over the African equatorial ionization anomaly using the rate of change of total electron content index. Irregularities were quantified in terms of percentage occurrence and examined along with parameter of the anomaly, mainly its strength and the asymmetry of the crests as well as equatorial electric field derived from the real‐time equatorial electric field model and meridional wind obtained from the horizontal wind model. Irregulari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The temporal and spatial resolution of the EIA maps obtained was 1 hour x 1 degree. We recall that there is a displacement of about 9 o between the magnetic equator and geographic equator within longitude 25 o -40 o E (Amaechi et al, 2020).…”
Section: Tec Derived From Gnss Measurements (Gnss-tec)mentioning
confidence: 94%
See 2 more Smart Citations
“…The temporal and spatial resolution of the EIA maps obtained was 1 hour x 1 degree. We recall that there is a displacement of about 9 o between the magnetic equator and geographic equator within longitude 25 o -40 o E (Amaechi et al, 2020).…”
Section: Tec Derived From Gnss Measurements (Gnss-tec)mentioning
confidence: 94%
“…Both years fall within the maximum phase of SC-24 with mean observed annual solar flux of 122.76 and 146.54 solar flux unit (s.f.u), respectively. A day was deemed quiet if its Kp was lesser or equal to 3 (Amaechi et al, 2020;Fejer et al, 2008).…”
Section: Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was likely due to the smaller background ionization in the postsunset period on 17 March (Figure 5). Several researchers have stressed on the role of background ionization and its relation to irregularities formation (Aarons et al., 1981; Amaechi et al., 2020b; Tulasi Ram et al., 2006; Wernik et al., 1983). A contributing factor could have been the morphology of the EIA discussed in the past section.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, on 21 March, the formation of irregularities might have been promoted by the northward return of IMF Bz in the night (Figure 2, panel 2). The few studies on the relation between the anomaly and irregularities over Africa had focused on seasonal trends of variations in the strength of the anomaly and latitudinal extent of the crests (Amaechi et al., 2020b) as well as the values of CTR (Seba et al., 2018) during quiet time. These studies mainly revealed the asymmetry of the anomaly in winter and summer.…”
Section: Discussionmentioning
confidence: 99%